Fabula - Henry, Patrick; Roberts, Russel; National Museum of Photography, Film & Television, Bradford (Bradford : National Museum of Photography, Film & Television, 2003)
Faust, Jeanne ; Gage, Jenny ; Hido, Todd ; Hulse, Matt ; Prouvost, Laure ; Stewart, Christopher ; Yaari, Sharon
National Museum of Photography, Film & Television, Bradford, 11 April - 15 June 2003.
kunstcatalogus